Предмет: Алгебра,
автор: sonia1717
Упростите выражение (2a+b)(4a^2^-2ab+b^2^)-8a(a+b)(a-b)
И найдите его значение при a= - 1/4 b=1
Ответы
Автор ответа:
0
(2a+b)(4a^2^-2ab+b^2^)-8a(a+b)(a-b)
6a^3-4a^2b+2ab^2+4a^2b-2ab^2-b^3-8a(2a-b^2)
8a^3+b^3-16a^2+8ab^2
0.125+1-1-2=-1,875
6a^3-4a^2b+2ab^2+4a^2b-2ab^2-b^3-8a(2a-b^2)
8a^3+b^3-16a^2+8ab^2
0.125+1-1-2=-1,875
Похожие вопросы
Предмет: Математика,
автор: mericamalova95
Предмет: Биология,
автор: Аноним
Предмет: Русский язык,
автор: ajzerebolathanova3
Предмет: Физика,
автор: Настя3498